2021
DOI: 10.1186/s13256-021-02751-3
|View full text |Cite
|
Sign up to set email alerts
|

Severe acute respiratory syndrome coronavirus-2- or pregnancy-related cardiomyopathy, a differential to be considered in the current pandemic: a case report

Abstract: Background There are limited data on cardiovascular complications of coronavirus disease 2019 in pregnancy, and there are only a few case reports on coronavirus disease 2019 related cardiomyopathy in pregnancy. Differentiation between postpartum cardiomyopathy and coronavirus disease 2019 related cardiomyopathy in pregnant women who develop severe acute respiratory syndrome coronavirus-2 infection during peripartum could be challenging. Here, we present a case of possible coronavirus disease 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Moreover, Bhattacharyya et al reported a case of Takotsubo cardiomyopathy at the 38th week of pregnancy [ 56 ]. In a case of a young pregnant woman reported by Nejadrahim et al, cardiomiopathy with a left ventricular ejection fraction of 40% was observed [ 57 ]. Soofi et al reported acute heart failure and venous thrombosis in a case of a 25-year-old pregnant women infected with SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Bhattacharyya et al reported a case of Takotsubo cardiomyopathy at the 38th week of pregnancy [ 56 ]. In a case of a young pregnant woman reported by Nejadrahim et al, cardiomiopathy with a left ventricular ejection fraction of 40% was observed [ 57 ]. Soofi et al reported acute heart failure and venous thrombosis in a case of a 25-year-old pregnant women infected with SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
“…In one series of 113 deceased patients, CHF occurred in one quarter of non-pregnant COVID-19 patients [ 49 ]. Cardiomyopathies among pregnant COVID-19 patients may be due to a peripartum [ 50 , 51 ], sepsis or stress mediated (Takotsubo) cardiomyopathy [ 52 ]. Peripartum cardiomyopathy (PPCM) is a diagnosis of exclusion and differentiating between PPCM and COVID-19 mediated cardiomyopathy may prove to be clinically challenging.…”
Section: Covid-19 and Cardiac Involvement In Pregnancymentioning
confidence: 99%
“…Differentiating between postpartum cardiomyopathy and COVID-19-related cardiomyopathy in infected pregnant women is challenging. The case of a young pregnant woman who exhibited signs of heart failure with pulmonary edema following cesarean section has been presented in the literature [ 57 ]. Coagulopathy is considered to be associated with COVID-19, which in turn may result in the onset of further complications, including deep vein thrombosis [ 58 ].…”
Section: Complications Of Covid-19 Reported In Pregnancymentioning
confidence: 99%